MlCROPALEODOLOGICAL STUDY OF CORE Z1 FROM IONIAN SEA PALEOCLIMATOLOGICAL- PALEOOICOLOGICAL CONCLUSIONS - Γεραγά, Μ.; Μυλωνά, Γ.; Τσαϊλά-Μονόπωλη, Στ.; Παπαθεοδώρου, Γ.; Φερεντίνος, Γ. (Bulletin of the Geological Society of Greece, 2018)
The preliminary results based on the abundances of planktonic foraminifera and oxygen isotopes at the sediments of the core Z1, selected from the Ionian Sea (Otranto Basin) revealed three main climatic periods: Last Glacial, Late Glacial and Holocene. The warmest conditions of the studied interval prevailed during the formation of sapropel S1. Four stadials occurred during Late Glacial and Holocene. The older corresponds to Younger Dryas event, while the other three occurred during Holocene. The establishment of warm and low salinity surficial waters seems that caused the reduction of water mass circulation and thus the formation of the sapropel S1. Although the presence of a stadial around the middle of the S1, no distinct interruption of the sapropelic sedimentation have been occurred. The younger stadial coincides with the end of the sapropel S1. The evolution of the planktonic assemblages seems to be similar with that of the Central Mediterranean for the studied interval. Therefore, almost all the biozones and ecozones of the Central Mediterranean have been recognized at the sediments of Z1. The application of the factor analysis revealed four factors. The first two correspond to the variation of SST, while the other two are related to the development of high fertility waters during cold periods and during the formation of S1.